Cultured meat in western media: The disproportionate coverage of vegetarian reactions, demographic realities, and implications for cultured meat marketing - Patrick D Hopkins (Journal of Integrative Agriculture, 2015)
This paper examines the media coverage of the 2013 London cultured meat tasting event, particularly in the United States, Canada, and the United Kingdom. Using major news outlets, prominent magazines covering food and science issues, and advocacy websites concerning meat consumption, the paper characterizes the overall emphases of the coverage, the tenor of the coverage, and compares the media portrayal of the important issues to the demographic and psychological realities of the actual consumer market into which cultured meat will compete. In particular, the paper argues that Western media gives a distorted picture of what obstacles are in the path of cultured meat acceptance, especially by overemphasizing and overrepresenting the importance of the reception of cultured meat among vegetarians. Promoters of cultured meat should recognize the skewed impression that this media coverage provides and pay attention to the demographic data that suggests strict vegetarians are a demographically negligible group. Resources for promoting cultured meat should focus on the empirical demographics of the consumer market and the empirical psychology of mainstream consumers.